PENGEMBANGAN MEDIA " KALENG INDAH" UNTUK MENINGKATKAN KARAKTER PEDULI LINGKUNGAN SISWA DI SDN LEBAK WANGI KABUPATEN TANGERANG - Mawardi; Siti Putri Fitriah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to develop “Kaleng Indah” learning media based on recycling to improve elementary school students’ environmental care character. This study uses the Research and Development (R&D) method with the ADDIE development model, consisting of analysis, design, development, implementation, and evaluation stages. The subjects included material experts, media experts, teachers, and students at SDN Lebak Wangi, Tangerang Regency. Data were collected through observation, interviews, and assessment questionnaires. Data analysis used quantitative and qualitative descriptive techniques. The results showed that “Kaleng Indah” media obtained a feasibility level of 90% from media experts, 95% from material experts, and 95% from teachers’ assessment, categorized as Highly Feasible. The application of this media provided direct learning experiences that effectively improved students’ awareness, creativity, and environmentally responsible behavior. This media also supports the implementation of the Merdeka Curriculum, especially the Pancasila Student Profile Strengthening Project on the theme of Sustainable Lifestyle.